2017
DOI: 10.1007/s10792-017-0595-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracorneal ring segment depth in keratoconus patients: a long-term follow-up study

Abstract: The mean 26 months after implantation, ring segments are placed at a shallower depth than originally intended. Therefore, although femtosecond laser technology is an acceptable method for the surgeon, it is necessary to revisit the depth calculator of the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…36 However, longer follow-ups are needed to provide consistent conclusions about the positional stability of ring segments within the corneal structure. Indeed, Shahhoseini et al 20 demonstrated in a retrospective study that ring segments were placed at a shallower depth than originally intended at 26 months after their implantation. More studies concerning this issue are still needed to obtain consistent conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 However, longer follow-ups are needed to provide consistent conclusions about the positional stability of ring segments within the corneal structure. Indeed, Shahhoseini et al 20 demonstrated in a retrospective study that ring segments were placed at a shallower depth than originally intended at 26 months after their implantation. More studies concerning this issue are still needed to obtain consistent conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, the depth of implantation of the ring segment is not considered in nomograms of ICRS implantation in spite of being the parameter that affects the corneal optics the most according to simulations used in silico models. 8 Currently, the use of the femtosecond laser technology allows the creation of tunnels for ICRS insertion at a predictable depth, 20 although long-term changes in this depth can occur possibly due to biomechanical or structural modifications and the scrubbing habit of these patients that can modify the position of the rings. 21,22 The aim of the current study was to analyze and characterize the impact of the depth of implantation of ICRS on morphological, biomechanical, and clinical outcomes obtained in ectatic corneas.…”
Section: Introductionmentioning
confidence: 99%
“…In eyes treated with traditional Dresden protocol, the depth of the demarcation line is approximately 300 µm [35] and shallower in accelerated CXL. AS-OCT also helpful in the evaluating the depth of implantation of intrastromal ring segments [36,37].…”
Section: Keratoconusmentioning
confidence: 99%
“…[ 15 ] In keratoconus patients, AS-OCT is found useful for qualitative evaluation of the cornea before and after implantation of the intrastromal ring. [ 18 ] AS-OCT is found useful to evaluate the Descemet's membrane tear, dimensions of intrastromal clefts, and corneal thickness in acute corneal hydrops of keratoconus [ Fig. 1 ].…”
Section: Keratoconus Diagnosis and Treatmentmentioning
confidence: 99%